PERLINDUNGAN SOSIAL ADAPTIF DAN MEKANISME PENYALURAN BANTUAN SOSIAL: STUDI KASUS PROGRAM KELUARGA HARAPAN (PKH) DI KOTA GORONTALO [ADAPTIVE SOCIAL PROTECTION AND SOCIAL ASSISTANCE DISTRIBUTION MECHANISM: CASE STUDY OF FAMILY HOPE PROGRAM (PKH) IN GORONTALO CITY] - Natsir, Nasrah; Arsyad, Yolandika; Rahmawati, Rahmawati (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
The purpose of this qualitative study is to analyze the implementation of the Program Keluarga Harapan (PKH) during the post-COVID-19 economic recovery period. PKH is a national conditional cash transfer program aimed at supporting extremely poor households. This study is guided by the principles of adaptive social protection, namely: 1) Promoting coordination among social protection institutions and disaster management stakeholders; 2) Ensuring that the scale of the program can respond to extreme situations; 3) Targeting the most vulnerable groups affected by disasters; 4) Designing programs that strengthen the adaptive capacities of households and communities; and 5) Ensuring rapid program response in specific situations, including pandemic-related crises. Informants in this study include program beneficiaries, program facilitators, the PKH coordinator in Gorontalo City, and representatives from the Social Welfare Office. The study examines the delivery mechanism of PKH assistance through in-depth interviews. The findings reveal that: 1) The cash transfer delivery mechanism improved, changing from a quarterly to a bimonthly schedule. This was intended to provide better financial security for beneficiaries in light of increasing economic pressure; 2) The types of services provided were expanded, from previously non-cash assistance to include Non-Cash Food Assistance and Socio-Economic Empowerment Programs; 3) The program coverage was broadened to reach more beneficiaries. Despite these positive changes, problems with targeting in the forms of exclusion and inclusion errors remain exist and this can have impact on the effectiveness of the program.